2016
DOI: 10.1080/17441730.2015.1128230
|View full text |Cite
|
Sign up to set email alerts
|

Parental Migration, Intergenerational Obligations and the Paradox for Left-Behind Boys in Rural China

Abstract: Drawing on in-depth interviews with caregivers of left-behind children (LBC) in rural China, this article seeks to explore their understanding of migration motives and the social process of taking on care-giving roles for LBC. The authors argue that there are underlying socio-cultural explanations pertaining to economic motives for migration; such as, making contributions to social events (weddings and funerals) in village life, and fulfilling social obligations for left-behind sons' futures. Parents migrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Thus, in many rural areas, a patrilineal bias that privileges sons rather than daughters within the same household can still be seen. In a study of caregivers of left-behind children in rural China, N. Zhang et al (2016) found a patrilineal bias favoring paternal grandparents as caregivers for grandchildren. This was largely because the maternal grandmothers in their sample had multiple adult children and gave priority to looking after sons' children instead of daughters' children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in many rural areas, a patrilineal bias that privileges sons rather than daughters within the same household can still be seen. In a study of caregivers of left-behind children in rural China, N. Zhang et al (2016) found a patrilineal bias favoring paternal grandparents as caregivers for grandchildren. This was largely because the maternal grandmothers in their sample had multiple adult children and gave priority to looking after sons' children instead of daughters' children.…”
Section: Discussionmentioning
confidence: 99%
“…Although weakened patrilineal norms in upward flows of assistance are well documented as manifested in more and more married daughters living with their own parents and providing at least as much of the elder care as their male counterparts (Shi, 2009;Whyte, 2005;Xie & Zhu, 2009), several studies have shown that both monetary and time transfer from parents' downward transfer to adult children still reflects a son-biased norm (Hu, 2017;Jiang, Li, & Feldman, 2015;N. Zhang, Chandola, Becares, & Callery, 2016).…”
Section: Gender Asymmetrical Patterns Of Transfermentioning
confidence: 99%
“…Therefore, in case of food scarcity, boys may be more likely to be suffered than girls. Another possible explanation might be due to socio-cultural obligation for boys in rural China that parents tend to save up for son’s adult lives instead of investing in their nutrition, while there is less pressure for girls [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that living in more urbanized areas can be more detrimental for boys than for girls. One possible explanation may be due to the socio-cultural norm of ‘son preference’ whereas sons are more culturally valued and tend to be allocated more resources than daughters [ 39 – 41 ]. Another possible explanation may be that adolescent boys are more prone to develop risky cardiovascular health behaviors such as poorer dietary habits, less physical activity, and higher odds of smoking that can be associated with poor neighborhood contexts [ 49 ] .…”
Section: Discussionmentioning
confidence: 99%
“…All models were adjusted for family socioeconomic circumstances in terms of maternal education and household income per capita to remove potentially confounding effects. All analyses were stratified by gender given the specific socio-cultural context of China where boys tend to be more valued and given more resources [ 39 – 41 ].…”
Section: Methodsmentioning
confidence: 99%